Chromosome-level genome assembly of Cylas formicarius provides insights into its adaptation and invasion mechanisms - Jin-feng HUA; Lei ZHANG; Yong-hua HAN; Xiao-wan GOU; Tian-yuan CHEN; Yong-mei HUANG; Yan-qing LI; Dai-fu MA; Zong-yun LI (Journal of Integrative Agriculture, 2023)
Cylas formicarius is one of the most important pests of sweet potato worldwide, causing considerable ecological and economic damage. This study improved the effect of comprehensive management and understanding of genetic mechanisms by examining the functional genomics of C. formicarius. Using Illumina and PacBio sequencing, this study obtained a chromosome-level genome assembly of adult weevils from lines inbred for 15 generations. The high-quality assembly obtained was 338.84 Mb, with contig and scaffold N50 values of 14.97 and 34.23 Mb, respectively. In total, 157.51 Mb of repeat sequences and 11 907 protein-coding genes were predicted. A total of 337.06 Mb of genomic sequences was located on the 11 chromosomes, accounting for 99.03% of the total length of the associated chromosome. Comparative genomic analysis showed that C. formicarius was sister to Dendroctonus ponderosae, and C. formicarius diverged from D. ponderosae approximately 138.89 million years ago (Mya). Many important gene families expanded in the C. formicarius genome were involved in the detoxification of pesticides, tolerance to cold stress and chemosensory system. To further study the role of odorant-binding proteins (OBPs) in olfactory recognition of C. formicarius, the binding assay results indicated that CforOBP4–6 had strong binding affinities for sex pheromones and other ligands. The high-quality C. formicarius genome provides a valuable resource to reveal the molecular ecological basis, genetic mechanism, and evolutionary process of major agricultural pests; it also offers new ideas and new technologies for ecologically sustainable pest control.